1997
DOI: 10.1038/hdy.1997.170
|View full text |Cite
|
Sign up to set email alerts
|

The ten cytological races of the Scilla autumnalis species complex

Abstract: Scilla autumnalis, a bulbaceous perennial member of the Liliaceae, is widespread throughout much of Europe and North Africa. So far it has been classified as a single species, primarily on morphological grounds. This paper reports 10 cytologically distinct races of the plant present over the range of distribution, and hypothesizes the existence, at least at some stage of the evolution of the complex, of two additional races. At least five distinct genornes are described, involving chromosomal rearrangements, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 19 publications
0
24
1
Order By: Relevance
“…armena (Table 2). Vaughan et al (1997) reported that the taxonomic status and relationships of S. autumnalis were no clear, because of widespread (the Mediterranean, South-Western England, Portugal, Libya and North Africa). So, he called it as S. autumnalis species complex.…”
Section: Armena) and Unifacial (S Melaina Sleepii S Ingridae Smentioning
confidence: 99%
See 1 more Smart Citation
“…armena (Table 2). Vaughan et al (1997) reported that the taxonomic status and relationships of S. autumnalis were no clear, because of widespread (the Mediterranean, South-Western England, Portugal, Libya and North Africa). So, he called it as S. autumnalis species complex.…”
Section: Armena) and Unifacial (S Melaina Sleepii S Ingridae Smentioning
confidence: 99%
“…S. autumnalis has widespread distribution in Turkey, Mediterranean, South-Western England, Portugal, Libya and North Africa. Vaughan et al (1997) reported it as complex or cryptic species. However, it was critically endangered in some countries (specially, Romania) and was taken into protection in Romania (Banciu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has been described as a complex and cryptic species (Vaughan et al, 1997). S. autumnalis is not under threat in Turkey (including within the Kuşadası-Marmaris localities), but it is critically endangered in some countries especially Romania (Banciu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…7 [Vaughan et al, 1997;Jang et al, 2013] possess a basic chromosome number of x = 7 but differ in genome size, with cytotype AA having a 70% larger genome than B 7 B 7 (1C of 7.85 pg and 4.23/4.45 pg, respectively) [Jang et al, 2013]. Cytotypes B , endemic to Libya, underwent independent reductions of base chromosome numbers to x = 6 and x = 5, respectively, as well as increases of genome sizes (1C of 6.27 pg and 4.68 pg, respectively) [Jang et al, 2013].…”
mentioning
confidence: 99%
“…data]. Although the 4 cytotypes form phylogenetically distinct groups [Jang et al, 2013] genomes), and autopolyploids originating from the B 7 genome [Vaughan et al, 1997]. In addition, all diploid cytotypes can be crossed and produce viable diploid homoploid hybrids [Taylor, 1997;Jang et al, 2013].…”
mentioning
confidence: 99%